A extensão nos Institutos Federais de Educação, Ciência e Tecnologia de Minas Gerais - Romário Geraldo (2015)
The main goal of this study is to analyze the process of construction of the extension in the Federal Institute of Education, Science and Technology. It presents the story of university extension, its consolidation in the legislation and educational reforms, the conceptions which influenced it and its struggle for conceptualizing it, institutionalizing it and financing it. It unravels the creation of the first public policies developed for the university extension in Brazil and highlights the effort for the organization and strengthening of extension, in order for it to consolidate itself in the university on the same level as teaching and research. The understanding of the context in which professionalizing education developed itself and of how it used the concepts of extension in its practice composes the investigation. To maintain analytical rigor in the purposes of this thesis, we analyze the social, economic, political and technical scientific changes, in parallel with the legal devices and the regulatory framework of the policies of the federal government regarding professionalizing education, ever since the beginning of its regulation in Brazil. Minas Gerais is chosen as the analytical space. The field research is based on the methodology of survey with the deans of university extension of the Federal Institutes and professors awarded with extension support notices of PROEXT and FAPEMIG during the period of 2010 to 2013, and it also has the background of bibliographic research and documentary sources. Specifically, it investigates the origin, the actions, the objectives and the concepts of extension throughout its story in the country. The organization and the operation of the mechanisms of institutional, administrative, infrastructural and financial order that hold back the practice of extension in the Federal Institutes complete the range of the study. The empirical search is put against the theoretical references and it establishes a comparison between what legislation says and what is actually done.